Environmental versus geographical effects on genomic variation in wild soybean (Glycine soja) across its native range in northeast Asia. Issue 17 (14th August 2016) - Leamy, Larry J.; Lee, Cheng‐Ruei; Song, Qijian; Mujacic, Ibro; Luo, Yan; Chen, Charles Y.; Li, Changbao; Kjemtrup, Susanne; Song, Bao‐Hua
Abstract: A fundamental goal in evolutionary biology is to understand how various evolutionary factors interact to affect the population structure of diverse species, especially those of ecological and/or agricultural importance such as wild soybean ( Glycine soja ). G. soja, from which domesticated soybeans ( Glycine max ) were derived, is widely distributed throughout diverse habitats in East Asia (Russia, Japan, Korea, and China). Here, we utilize over 39, 000 single nucleotide polymorphisms genotyped in 99 ecotypes of wild soybean sampled across their native geographic range in northeast Asia, to understand population structure and the relative contribution of environment versus geography to population differentiation in this species. A STRUCTURE analysis identified four genetic groups that largely corresponded to the geographic regions of central China, northern China, Korea, and Japan, with high levels of admixture between genetic groups. A canonical correlation and redundancy analysis showed that environmental factors contributed 23.6% to population differentiation, much more than that for geographic factors (6.6%). Precipitation variables largely explained divergence of the groups along longitudinal axes, whereas temperature variables contributed more to latitudinal divergence. This study provides a foundation for further understanding of the genetic basis of climatic adaptation in this ecologically and agriculturally important species. Abstract : We utilize genome‐wide single nucleotide polymorphism data in 99 ecotypes of Glycine soja, sampled across their native geographic range in northeast Asia, to understand population structure and the relative contribution of environment versus geography to population differentiation in this species. We further identified the environmental factors that have shaped genetic variation using canonical correlation and redundancy analyses in this ecologically and economically important species.